The pathophysiology of cardiac surgery-associated acute kidney injury (CSA-AKI) - Bellomo, R; Auriemma, S; Fabbri, A; D'Onofrio, A; Katz, N; McCullough, P A; Ricci, Z; Shaw, A; Ronco, C (International journal of artificial organs, 2008)
Cardiac surgery associated acute kidney injury (CSA-AKI) is a significant clinical problem. Its pathogenesis is complex and multifactorial. It likely involved at least six major injury pathways: exogenous and endogenous toxins, metabolic factors, ischemia and reperfusion, neurohormonal activation, inflammation and oxidative stress. These mechanisms of injury are likely to be active at different times with different intensity and probably act synergistically. Because of such complexity and the small number of randomised controlled investigations in this field only limited recommendations can be made. Nonetheless, it appears important to avoid nephrotoxic drugs and desirable to avoid hyperglycemia in the peri-operative period. The duration of cardiopulmonary bypass should be limited whenever possible. Off-pump surgery, when indicated, may decrease the risk of AKI. Invasive hemodynamic monitoring focussed on attention to maintaining euvolemia, an adequate cardiac output and an adequate arterial blood pressure is desirable. Echocardiography may be useful in minimizing atheroembolic complications. The administration of N-acetylcysteine to protect the kidney from oxidative stress is not recommended. There is marked lack of randomised controlled trials in this field.